1960
DOI: 10.1111/j.1476-5381.1960.tb01242.x
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Accumulation of Bretylium in Sympathetic Ganglia and Their Postganglionic Nerves

Abstract: A study of the distribution of [14C]-labelled bretylium (N-o-bromobenzyl-N ethyl-NN-dimethylammonium) in cat tissues at various times after subcutaneous injection suggests that the specificity of its blocking action on adrenergic neurones may be related to its selective accumulation in these neurones. The rate of rise and fall of concentration in sympathetic ganglia and postganglionic sympathetic nerves showed a close similarity to the time course of the blocking adrenergic neurones as manifested by relaxatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0

Year Published

1964
1964
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 7 publications
3
49
0
Order By: Relevance
“…In the same line Boura et al (2) and Bentley (3) have shown that the response is abolished by the addition of reserpine, guanethidine and bretylium. The enhancement of the response by the addition of carbamyl-choline has been shown by Bentley.…”
supporting
confidence: 54%
“…In the same line Boura et al (2) and Bentley (3) have shown that the response is abolished by the addition of reserpine, guanethidine and bretylium. The enhancement of the response by the addition of carbamyl-choline has been shown by Bentley.…”
supporting
confidence: 54%
“…Hexamethonium is a bis-quaternary compound, and would have more difficulty in entering a postganglionic sympathetic fibre than mono-quaternary compounds like bretylium or acetylcholine. From the work of Boura, Copp, Duncombe, Green & McCoubrey (1960) it is known that bretylium enters the postganglionic sympathetic fibre in cats, and observations by Stewart, Hutchinson & Szaz (unpublished) have shown that it enters the sympathetic fibres in man in the course of a few minutes.…”
Section: Discussionmentioning
confidence: 99%
“…One approach is to use bretylium to identify sympathetic nerve terminals. Bretylium enters sympathetic varicosities through uptake-1 sites where it acts as a local anaesthetic and blocks action potential propagation in the secretory terminals and hence transmitter release (Boura & Green, 1960;Brock & Cunnane, 1988b). Bretylium should therefore abolish action potential-evoked Ca 2+ transients in all varicosities containing uptake-1 sites.…”
mentioning
confidence: 99%